Analisis Hambatan Pembelajaran Biologi dalam Implementasi Kurikulum Merdeka di SMA Katolik St. Rosa De Lima Tondano - Gea, Aguslina; Semuel, Mokosuli Yeremia; Posumah, Dany Christian; N. Tanor, Meity; P. Gedoan, Sukmarayu; R. Kawuwung, Femmy (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the obstacles faced by biology teachers and students in the implementation of the Independent Curriculum at St. Rosa De Lima Catholic High School in Tondano. The Merdeka Curriculum emphasizes freedom of thought, project-based learning, and the development of critical and collaborative thinking skills, but its implementation still faces obstacles at the secondary school level. This study uses a descriptive qualitative approach with data collection techniques through observation, questionnaires, interviews, and documentation. The research subjects consisted of one biology teacher and ten students of class X. Data were analyzed descriptively, qualitatively, and quantitatively with percentage support to describe the level of resistance based on four main indicators: learning process, teaching materials, assessment, and curriculum information. The results of the study show that teachers' obstacles in the implementation of the Independent Curriculum are relatively low with an average of 18.6%, especially in terms of time management, limited laboratory facilities, and limited digital learning resources. In contrast, internal student factors such as interest, motivation, readiness, and attention had an average of 67.17%, while external factors included family, school environment, and community support at 55.5%. These findings indicate that the success of the implementation of the Independent Curriculum depends on the pedagogical readiness of teachers, the availability of learning facilities, and the support of a conducive learning environment. This research contributes to providing an empirical picture of the challenges of implementing the Independent Curriculum in biology learning and becomes the basis for the development of adaptive, collaborative, and student-centered learning strategies.